hVps15, but not Ca(2+)/CaM, is required for the activity and regulation of hVps34 in mammalian cells - Yan, Ying (Portland Press Ltd., 2009)
The mammalian Class III PI3K (phosphoinositide 3-kinase), hVps34 [mammalian Vps (vacuolar protein sorting) 34 homologue], is an important regulator of vesicular trafficking, autophagy and nutrient sensing. In yeast, Vps34 is associated with a putative serine/threonine protein kinase, Vps15, which is required for Vps34p activity. The mammalian homologue of Vps15p, hVps15 (formerly called p150), also binds to hVps34, but its role in hVps34 signalling has not been evaluated. In the present study we have therefore compared the activity and regulation of hVps34 expressed without or with hVps15. We find that hVps34 has low specific activity when expressed alone; co-expression with hVps15 leads to a marked increase in activity. Notably, beclin-1/UVRAG (UV radiation resistance-associated gene) activation of hVps34 requires co-expression with hVps15; this may be explained by the observation that beclin-1/UVRAG expression increases hVps34/hVps15 binding. Regulation of hVps34 activity by nutrients also requires co-expression with hVps15. Finally, given a recent report that hVps34 activity requires Ca(2+)/CaM (calmodulin), we considered whether hVps15 might be involved in this regulation. Although hVps34 does bind CaM, we find its activity is not affected by treatment of cells with BAPTA/AM [1,2-bis-(o-aminophenoxy)ethane-N,N,N′,N′-tetra-acetic acid tetrakis(acetoxymethyl ester)] or W7. Removal of CaM by EDTA or EGTA washes has no effect on hVps34 activity, and hVps34 activity in vitro is unaffected by Ca(2+) chelation. The results of the present study show that, in mammalian cells, hVps34 activity is regulated through its interactions with hVps15, but is independent of Ca(2+)/CaM.